Chronic kidney disease and vitamin D metabolism in human bone marrow–derived MSCs - Zhou, Shuanhu; Glowacki, Julie (Annals of the New York Academy of Sciences, 2017)
Vitamin D that is synthesized in the skin or is ingested undergoes sequential steps of metabolic activation via a cascade of cytochrome P450 enzymatic hydroxylations in the liver and kidney to produce 1α,25‐dihydroxyvitamin D (1α,25(OH)2D). There are many tissues that are able to synthesize 1α,25(OH)2D, but the biological significance of extrarenal hydroxylases is unresolved. Human marrow‐derived mesenchymal stem cells (marrow stromal cells, hMSCs) give rise to osteoblasts, and their differentiation is stimulated by 1α,25(OH)2D. In addition to being targets of 1α,25(OH)2D, hMSCs can synthesize it; on the basis of those observations, we further examined the local autocrine/paracrine role of vitamin D metabolism in osteoblast differentiation. Research with hMSCs from well‐characterized subjects provides an innovative opportunity to evaluate the effects of clinical attributes on the regulation of hMSCs. Like the renal 1α‐hydroxylase, the enzyme in hMSCs is constitutively decreased with age and chronic kidney disease (CKD); both are regulated by PTH1‐34, insulin‐like growth factor 1, calcium, 1α,25(OH)2D, 25(OH)D, and fibroblast growth factor 23. CKD is associated with impaired renal biosynthesis of 1α,25(OH)2D, low bone mass, and increased fracture risk. Studies with hMSCs from CKD patients or aged subjects indicate that circulating 25(OH)D may have an important role in osteoblast differentiation on vitamin D metabolism and action in hMSCs.